Improving the publication activity of Ukrainian scientists: problems, solutions, the use of mathematical and statistical methods (Law and Safety, 2023)
Many Ukrainian and foreign scholars have been studying the problems of financing scientific activities for a long time. Moreover, such issues are even raised in the works of scholars from developed Western countries. The range of such studies is extremely wide: from analysing problems and violations of the above-mentioned principles of law to modelling innovative grant support systems, including those that model an equal and fair system. Foreign scientists mostly focus on the specifics of grant provision and its impact, improvement and innovation of the financial resource allocation system in the field of science, etc. In Ukraine, the vast majority of research is concerned with the comparative characteristics of the share of the gross domestic product allocated to science funding, general problems of international cooperation with foreign grant providers, improvement of the system of financial resources allocation in the field of science, etc. Unfortunately, no attention has been paid to specific mechanisms of rewarding publications in leading foreign scientific journals. This issue is no less important, since individual support for publication activity is a powerful “lever of encouragement” for researchers and academic staff, which directly affects the results of a particular institution in the chain of international and national rankings. In addition, such support contributes to the development of science, scientific and technological progress, and raises the country’s rating in the international arena.The article is devoted to the formulation of possible ways of solving the problem of proper State support and funding for publications of Ukrainian scholars in leading foreign professional journals in accordance with the following criteria: equal rights and opportunities to receive funding for publications in foreign professional journals from the State, regardless of age, gender, race, nationality, religious beliefs, social and property status, place of work, research topic, etc. funding for foreign professional publications is provided only to the scientist personally without the mediation of the institution where he/she works or third parties in order to increase his/her scientific efficiency and quality, to popularize Ukrainian science and to attract competitive international professionals to science; the funding of foreign professional publications should be set transparently.The mechanism for calculating the relevant funding has been formed. The definitions of the concepts “mechanism of state support and financing of publications of Ukrainian scientists in foreign professional journals included in leading international databases”, “leading international databases” and “foreign professional journal” have been proposed. The article analyses the publication activity (1996–2022) of Ukrainian scientists in scientific journals indexed in the international scientometric database Scopus.
Keywords: scientific and technical activities; funding, legislation; statistics; mathematical calculations; improvement of the regulatory framework.